2002
DOI: 10.1021/bi0263762
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Actin Dynamics by Tyrosine Phosphorylation:  Identification of Tyrosine Phosphorylation Sites within the Actin-Severing Domain of Villin

Abstract: We have previously shown that villin, an epithelial cell actin-binding protein, is tyrosine phosphorylated both in vitro and in vivo and that villin's actin-modifying functions are regulated by phosphorylation. Here as a first step toward understanding the role of villin tyrosine phosphorylation, we sought to identify the major phosphorylation site(s) in human villin and study its role in actin filament assembly. We generated a series of carboxyl-terminal truncation mutants of villin and cloned them in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
59
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(71 citation statements)
references
References 51 publications
(83 reference statements)
12
59
0
Order By: Relevance
“…The bottom panel in Figure 3B is an SDS-PAGE of VIL/WT and VILT/WT stained with GelCode Blue, showing the expression of the two recombinant proteins VILT/WT and VIL/WT. Consistent with our previous studies Zhai et al, 2002), tyrosine phosphorylation of villin (in response to wounding or treatment with HGF/EGF) is inhibited by PP2 but not PP3 ( Figure 3C). By using this approach, no basal tyrosine phosphorylation of villin in the absence of wounding or EGF/HGF treatment could be detected in these cells with either phospho-villin antibody (VP-70782) or phospho-tyrosine antibody .…”
Section: Tyrosine Phosphorylation Of Villin Is Essential For Villininsupporting
confidence: 92%
See 4 more Smart Citations
“…The bottom panel in Figure 3B is an SDS-PAGE of VIL/WT and VILT/WT stained with GelCode Blue, showing the expression of the two recombinant proteins VILT/WT and VIL/WT. Consistent with our previous studies Zhai et al, 2002), tyrosine phosphorylation of villin (in response to wounding or treatment with HGF/EGF) is inhibited by PP2 but not PP3 ( Figure 3C). By using this approach, no basal tyrosine phosphorylation of villin in the absence of wounding or EGF/HGF treatment could be detected in these cells with either phospho-villin antibody (VP-70782) or phospho-tyrosine antibody .…”
Section: Tyrosine Phosphorylation Of Villin Is Essential For Villininsupporting
confidence: 92%
“…Previous studies from our laboratory have demonstrated that villin is a substrate in vitro for the src kinase(s) Zhai et al, 2002). In addition, our studies have suggested that villin phosphorylation and the resulting changes in the actin rearrangements might serve to promote the migratory phenotype of epithelial cells Zhai et al, 2002).…”
Section: Tyrosine Phosphorylation Of Villin Is Essential For Villininmentioning
confidence: 56%
See 3 more Smart Citations